Analysis of Surface Integrity of Parts after Non Conventional Methods of Machining - Vajdová, Alena; Mičietová, Anna; Neslušan, Miroslav; Kolařik, Kamil (Manufacturing Technology Journal, 2014)
This paper deals with analysis of surface integrity of steel after electro discharge machining (EDM), water jet machining, (WJM) laser beam machining (LBM) and plasma beam machining (PBM). The paper discusses surface integrity expressed in surface roughness, sample precision expressed in perpendicularity deviation as well as stress state. This study also demonstrates influence of the various non conventional methods on structure transformations and reports about sensitivity of the different non conventional methods of machining with regard to variable thickness of machined samples.
Keywords: Equation; Manufacturing Technology; Pictures; Tables; Template